Respiratory syncytial virus and human metapneumovirus in severe lower respiratory tract infections in children under two - Othman, Heba Taher; Elhamed, Walaa Al Sharany Abu; Hassan, Dina Mohammed; Soliman, May Sherif; Abdel Baset, Radwa Wagih (The Journal of Infection in Developing Countries, 2016)
Introduction: Viruses are the most important causative agents of acute lower respiratory tract infections (ALRTIs), ranked as the second leading cause of death and the primary cause of hospitalization in children. Respiratory syncytial virus (RSV) and human metapneumovirus (hMPV) are among the commonest viral causes of severe ALRTI. In this study, we aimed to study the burden of both RSV and hMPV in causing severe ALRTI in children younger than two years of age admitted to the pediatric intensive care unit (PICU). Methodology: Nasopharyngeal swabs were collected from children admitted to the PICU with a diagnosis of community-acquired ALRTI who were two years of age or younger. Real-time polymerase chain reaction (RT-PCR) was used to test for RSV and hMPV. Results: A total of 127 swabs were screened for RSV and hMPV, of which 49.6% were negative for RSV and hMPV, 46.4% were positive for RSV, and 3.9% were positive for hMPV. With respect to RSV, the mean age of cases (4.01 ± 5.05) and the monthly distribution (mainly January) were the most important risk factors. There were no statistically significant differences between the RSV group and control group regarding duration of hospital stay, mechanical ventilation need or duration, and underlying chronic conditions. Conclusions: RSV is important viral cause of severe ALRTIs in children younger than two years of age during this study period; hMPV played a minor role.